Pathways to Opening Access to Agricultural Research Knowledge in India - Gutam, Sridhar; Attaluri, Srinivasacharyulu (Journal of Agricultural Extension Management, 2021)
New knowledge is created by analysing and processing data and information. Having access to data and information promotes the generation of science, the communication of science, and the creation and adoption of new knowledge. All Sustainable Development Goals (SDGs) include agriculture as an integral component, and agriculture should be prosperous and sustainable to achieve any SDG. Besides developing skilled and talented human resources, the Indian Agricultural Research System seeks to offer quality data and information to stakeholders to improve agricultural production, processing, and exports. However, access remains restricted despite the availability of data and information, making it impossible to achieve desired results. The purpose of this paper is to summarise how data, information and knowledge of NARS are available and accessible to various stakeholders during various phases of World Bank-supported projects and how the availability and accessibility to data and information exist in NARS